The One Belt One Road (OBOR) initiative and seaport business in Europe - perspective of the Port of Rijeka - Agatić, Adrijana (Array, 2019)
The OBOR-One Belt One Road initiative has potential to enable further development of the Port of Rijeka. The European seaports are important for China in the development of the OBOR initiative, especially the ports on the Maritime Silk Road (MSR) corridor of the OBOR. Chinese investors i.e. terminal operators in the past two decades have strategically invested in the European seaports to strengthen their position and obtain the OBOR goals. European seaports got the opportunity to improve their business through Chinese infrastructure investments and through China’s trade dominance which can bring more cargo to the European seaports. Thus, the OBOR i.e. Maritime Silk Road-MSR provide new possibilities for further development of the Port of Rijeka. The Chinese investors expressed their interest to invest in the Port of Rijeka, but concrete investments and collaboration regarding OBOR have not been realized. In this paper, the OBOR goals in Europe and the current status of OBOR in Europe will be identified. Strategic activities of China in the European seaports will be analyzed. The perspective the Port of Rijeka in the OBOR initiative i.e. MSR corridor will be elaborated according to the analyzed Chinese strategic activities in the European seaports and relevant aspects of the Port of Rijeka business: geo-traffic position, position on the OBOR corridors i.e. MSR corridor, membership in the NAPA – North Adriatic Port Association, shipping services and railway services, port infrastructure and investments.